'The only thing I "earned" in the damned war was PTSD.' Reconsidering veteran sociality and politics in Bosnia and Herzegovina. Issue 4 (2nd October 2018) - Klepal, Jaroslav
ABSTRACT: This article focuses on the monies that circulate in the system of veteran protection in the Federation of Bosnia and Herzegovina and shows that they are enacted in economically and morally conflicting ways. While the federal authorities treat the monies inconsistently, sometimes portraying them as compensation for service in the war, and other times branding them as dubious entitlements overused in the post-war years, ordinary war veterans, such as those living with posttraumatic stress disorder in the city of Tuzla where the author conducted ethnographic fieldwork, understand veterans' monies as a moral (and inviolable) entitlement rooted in their wartime experience. Besides these actors, there are also international creditors involved that denounce these monies as an economically harmful and corrupting gift. Current studies see veteran sociality and politics in post-Yugoslav conditions as a result of local post-war and post-socialist struggles for symbolic and material gains. However, this case foregrounds how veteran sociality and politics are also shaped by the interventions of international actors.